Endovascular management of the deep venous thrombosis: A new challenging role for the endovascular specialist in 2020. Issue 4 (13th November 2020) - Midulla, Marco; Chevallier, Olivier; Comby, Pierre‐Olivier; Giordano, Giuseppe; Pescatori, Lorenzo Carlo; Falvo, Nicolas; van den Berg, Jos C3; Cariati, Maurizio; Loffroy, Romaric
Abstract: Over the last years, the endovascular approach to the management of the acute and chronic deep vein thrombosis (DVT) has gained more and more attention from the scientific community. DVT is the third most common cardiovascular disease after coronary heart disease and stroke, with classic treatment based on anticoagulation. Recent evidences have highlighted the risk of postthrombotic syndrome as high as 30%–50% in proximal ilio‐femoral lesions, with irreversible clinical symptoms and impact on the quality of life of the population. Since 2000s, the new concept of thrombus removal in the acute phase has been supported by the introduction of different techniques based on the endovascular ablation of the clot by in‐situ fibrinolysis and, more recently, fragmentation and aspiration. In the chronic phase, recanalization of the thrombosed segment is recommended by stent placement to remove the obstruction and eventually reduce the congestion. Immediate technical success of these procedures is widely satisfying, whereas the long‐term clinical benefits are still debated. This paper presents an overview of the modern management of the DVT by endovascular approach with regard to the clinical contexts, interventional strategies and clinical outcomes. Endovascular specialist needs to be aware of this incoming challenge, as local expertise is demanded for the modern management of these patients in multidisciplinary theaters.